2018
DOI: 10.3389/fonc.2018.00305
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Profiling to Discover Mechanisms of Exceptional Response to Cabozantinib Plus Panitumumab in a Patient With Treatment Refractory Metastatic Colorectal Cancer

Abstract: MET amplification is rare in treatment-naïve metastatic colorectal cancer (CRC) tumors, but can emerge as a mechanism of resistance to anti-EGFR therapies. Preclinical and clinical data suggest that patients with MET amplified tumors benefit from MET-targeted therapy. Cabozantinib is an inhibitor of multiple tyrosine kinases, included c-MET. Panitumumab is an inhibitor of EGFR. This report describes a patient with KRAS, NRAS, and BRAF wild-type metastatic CRC who experienced disease progression on all standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…With the aim of getting a better understanding of the mechanisms of resistance to HER2-directed and EGFR-directed therapies, it has been recently reported that increased expression of MUC1 and MET , decreased expression of PTEN , and an activating mutation in PIK3CA is accompanied with HER2 -amplified in mCRC. These findings strongly highlight the molecular heterogeneity of the resistance to anti-EGFR therapy [39,46,49,50,51,52].…”
Section: Acquired Resistance To Anti-egfr Treatment In Crc Patientsmentioning
confidence: 90%
See 1 more Smart Citation
“…With the aim of getting a better understanding of the mechanisms of resistance to HER2-directed and EGFR-directed therapies, it has been recently reported that increased expression of MUC1 and MET , decreased expression of PTEN , and an activating mutation in PIK3CA is accompanied with HER2 -amplified in mCRC. These findings strongly highlight the molecular heterogeneity of the resistance to anti-EGFR therapy [39,46,49,50,51,52].…”
Section: Acquired Resistance To Anti-egfr Treatment In Crc Patientsmentioning
confidence: 90%
“…All these data support a role for MET in the generation of an acquired resistance to cetuximab in CRC patients. According to this, in vitro studies demonstrated that HGF-mediated Met activation prevented cetuximab-induced apoptosis or cell cycle arrest in CRC cells [39,51,52]. Preclinical and clinical data suggest that patients with amplified MET in tumors benefit from MET-targeted therapy.…”
Section: Acquired Resistance To Anti-egfr Treatment In Crc Patientsmentioning
confidence: 99%
“…Similarly, a case report of a treatment refractory patient with metastatic colorectal cancer showed that MET amplification was detected in ctDNA using next-generation sequencing, but not in tissue biopsy samples. The significant response that the patient experienced after treatment with the combination of cabozantinib plus panitumumab led to the suggestion that MET amplification in ctDNA may be a predictive biomarker for response [244]. Finally, in NSCLC, a recent study demonstrated the potential clinical utility of ctDNA as a guide for therapy when tissue DNA was insufficient or unavailable [240].…”
Section: Vi-b-circulating Tumor Dnamentioning
confidence: 99%
“…In the past two decades, systemic chemotherapy b one of the foremost choices for advanced CRC treatment 36. Recently, molecule-targeted agents, such as cetuximab,37 panitumumab,38,39 bevacizumab,40 regorafenib41,42 and ramucirumab,43,44 that inhibit RTKs activation have been approved for use in CRC treatment. Downregulation of RTKs’ activity can attenuate tumor cell growth, metastasis, and angiogenesis 4547.…”
Section: Discussionmentioning
confidence: 99%